A service-free wireless sensor solution - Tay, Timothy Kok Hooi (2017)
This project entails designing a service-free wireless sensor solution, powered by energy harvesting. Through the setting up of a security system, this project explores the future of service-free wireless sensors in buildings and industrial automation. This report discusses the numerous options available to make this security system a reality, as well as the considerations made to arrive at the final product. All descriptions, specifications, diagrams, and calculations required through the course of designing the service-free wireless sensor solution are mentioned in this report.